Risk factors for infectious complications after total elbow arthroplasty - A. A. Boyarov; A. V. Ambrosenkov; A. G. Aliev; R. M. Tikhilov; I. I. Shubnyakov (Вестник хирургии имени И.И. Грекова, 2022)
INTRODUCTION. Total elbow arthroplasty (TEA) is a good alternative surgical solution for many patients with severe traumatic and inflammatory joint injuries. However, this surgical procedure is characterized by a rather high incidence of periprosthetic joint infection (PJI): from 3 to 8 %. At present, the issue of the influence of various factors on the risk of PJI is relevant.The OBJECTIVE of the study was to identify risk factors for the development of PJI after primary TEA.METHODS AND MATERIALS. In a retrospective study, the data of 485 patients who underwent primary and revision TEA from 2003 to 2019 were analyzed. The total number of studied patients was divided into 2 groups. The main group consisted of 51 patients who underwent revision TEA for PJI. The control group included 434 patients who underwent primary TEA.RESULTS. Evaluation of the effect of the primary diagnosis on the risk of PJI development showed a statistically significant relationship only in patients with gunshot wounds of the elbow joint (p=0.01). In the study of possible anamnestic factors, the following were significant: a history of previous interventions on elbow joint (p=0.004), previous infection (p <0.001) and open fracture of the elbow (p=0.009).CONCLUSION. In the course of the study, we proved the influence of anamnestic factors in the occurrence of PJI. Performing a two-stage revision allows stopping the infectious process with high efficiency in most cases.